Selective Stiffening in Soft Actuators by Triggered Phase Transition of Hydrogel‐Filled Elastomers. (28th May 2021) - Visentin, Francesco; Murali Babu, Saravana Prashanth; Meder, Fabian; Mazzolai, Barbara
Abstract: Nature has inspired a new generation of robots that not only imitate the behavior of natural systems but also share their adaptability to the environment and level of compliance due to the materials used to manufacture them, which are typically made of soft matter. In order to be adaptable and compliant, these robots need to be able to locally change the mechanical properties of their soft material‐based bodies according to external feedback. In this work, a soft actuator that embodies a highly controllable thermo‐responsive hydrogel and changes its stiffness on direct stimulation is proposed. At a critical temperature, this stimulation triggers the reversible transition of the hydrogel, which locally stiffens the elastomeric containment at the targeted location. By dividing the actuator into multiple sections, it is possible to control its macroscopic behavior as a function of the stiffened sections. These properties are evaluated by arranging three actuators into a gripper configuration used to grasp objects. The results clearly show that the approach can be used to develop soft actuators that can modify their mechanical properties on‐demand in order to conform to objects or to exert the required force. Abstract : A thermo‐responsive hydrogel is used to locally induce phase transitions in an elastic containment to control stiffening of a soft pneumatic actuator. The results show promising increases in performance of up to 160% compared to similar actuators and show that such material combinations open the way for new soft devices that can tune their properties and macroscopic behaviors.